?KINETICS OF ILMENITE DISSOLUTION BY HYDROFLUORIC ACID (Biological Sciences - PJSIR, 1998)
The leaching behaviours of titanium and iron values were examined in hydrofluoric acid solutions of various strengths attemperatures of 60 to 80nC. The rate was linearlydependent on the HFconcentration but inversely proportional to the particle size of the ilmenite. Titanium leaching occurred at a much faster rate than iron leaching and the leaching rates of both were independent of the stirring speed over the range 0-400 rpm. The observed effects of the relevant operating variables on the dissolution rates were consistent with a kinetic model for chemical reaction control. The apparent activation energy for titanium dissolution was 51.08 kJ mol:' and 53.90 kJ rnol' for iron dissolution.